PENGARUH BEASISWA KARTU INDONESIA PINTAR KULIAH MERDEKA TERHADAP PERILAKU BELAJAR MAHASISWA UNIVERSITAS IBRAHIMY SITUBONDO - Moh. Hafid; Ach. Zukin (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
In an effort to achieve educational goals both quantitatively and qualitatively, the cost of education has a very decisive role. Therefore, without adequate financial support, the education process will not run as expected. The central government through the Ministry of Education, Culture, Research and Technology, in addition to channeling funds to complement higher education facilities and infrastructure, the government also provides funds to students in the form of scholarships, both underprivileged scholarships and achievement scholarships for students who have good achievements on campus. The provision of these scholarships is to provide motivation to students to improve learning outcomes and also to provide motivation to students who excel in order to maintain their achievements. The research method used is descriptive quantitative method. The research location is at Ibrahimy Situbondo University for students who are recipients of the Indonesia Smart College Card Scholarship. This study aims to determine how much influence the awarding of the Indonesia Smart College Card scholarship has on student Learning Behavior, and to determine the Learning Behavior of students who receive the Indonesia Smart College Card Scholarship. There are two variables in this study, namely scholarships (X) and learning behavior (Y). In this study, 108 scholarship recipient students were used as the population and the sample used was 29 students who received the Smart Indonesia Card Scholarship. The instruments in the research were questionnaire guidelines to obtain scores for awarding scholarships and questionnaire guidelines to obtain scores for student learning behavior in the Islamic Religious Education Study Program.